Persistence of Candida species in the respiratory tract of cystic fibrosis patients - Muthig, Michaela; Hebestreit, Alexandra; Ziegler, Uwe; Seidler, Marc; Müller, Frank-Michael (Medical mycology, 2010)
It is still controversial as to whether Candida spp. are transient or persistent colonizers of the respiratory tract of cystic fibrosis (CF) patients. We conducted a prospective study of 56 CF patients over a 30 month period to assess the distribution and persistence of different Candida spp. In vitro antifungal susceptibility testing was performed and the C. albicans isolates were typed with CARE-2 hybridization and other Candida spp. by RAPD-PCR for persistence and transmission. We found that the mean persistence of the most frequent Candida spp. was ≥ 9 months. In patients from whom more than 10 isolates were recovered, we noted that at least 30% were genetically related and transmission of C. albicans in siblings was observed. The majority of all isolates were susceptible to all antifungals tested. We concluded that there was long-term persistence of Candida in the respiratory tract of CF patients and that transmission between siblings may be one possible means of acquisition. Whether long-term colonization with Candida strains can contribute to the chronic infection and inflammation in the CF lung requires further investigation.